Encounter rates and engagement times limit the transmission of conjugative plasmids. - Jorge Rodriguez-Grande; Yelina Ortiz; Daniel Garcia-Lopez; M Pilar Garcillán-Barcia; Fernando de la Cruz; Raul Fernandez-Lopez (PLoS Genetics)
Plasmid conjugation is a major route for the dissemination of antibiotic resistances and adaptive genes among bacterial populations. Obtaining precise conjugation rates is thus key to understanding how antibiotic resistances spread. Plasmid conjugation is typically modeled as a density-dependent process, where the formation of new transconjugants depends on the rate of encounters between donor and receptor cells. By analyzing conjugation dynamics at different cell concentrations, here we show that this assumption only holds at very low bacterial densities. At higher cell concentrations, conjugation becomes limited by the engagement time, the interval required between two successful matings. Plasmid conjugation therefore follows a Holling´s Type II functional response, characterized by the encounter rate and the engagement time, which represent, respectively, the density and frequency-dependent limits of plasmid transmission. Our results demonstrate that these parameters are characteristic of the transfer machinery, rather than the entire plasmid genome, and that they are robust to environmental and transcriptional perturbation. Precise parameterization of plasmid conjugation will contribute to better understanding the propagation dynamics of antimicrobial resistances.